2022
DOI: 10.18778/1733-8077.2.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Career Coupling: Career Making in the Elite World of Musicians and Scientists

Abstract: This article analyzes the interaction between the careers of people working in artistic and intellectual worlds. Two ethnographic studies constitute the basis for the analysis of career building in connection with the careers of other actors. The concept of career coupling represents the process by which professional success is achieved through the forging of relationships between novice and elite actors. Career coupling in the social world of virtuoso musicians is compared to that of career coupling in the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…Se, como vimos, a construção da identidade profissional é um contínuo que irá se estender ao longo da vida de cada um deles, passamos à discussão de A presença de um vínculo forte entre as figuras do professor e do aluno, portanto, é bastante documentada em pesquisas que acatam os universos esportivo, intelectual, universitário e científico (CAMPBELL, 2003;SCHNAIBERG, 2005;RESKIN, 1979;WAGNER, 2006). Ao revisar esses e outros estudos que tratam de tal relação, Izabella Ao tratar da realização musical instrumental sob a ótica do movimento humano, Flora Maria Gomide Vezzá (2013, p. 15), afirma que "o corpo do músico posiciona-se para produzir um movimento que contenha em si as características da música -sonoridade, afinação, melodia, ritmo, expressividade, sentimento".…”
Section: O Acesso a Instituições De Ensino E O Vínculo Professor-alun...unclassified
“…Se, como vimos, a construção da identidade profissional é um contínuo que irá se estender ao longo da vida de cada um deles, passamos à discussão de A presença de um vínculo forte entre as figuras do professor e do aluno, portanto, é bastante documentada em pesquisas que acatam os universos esportivo, intelectual, universitário e científico (CAMPBELL, 2003;SCHNAIBERG, 2005;RESKIN, 1979;WAGNER, 2006). Ao revisar esses e outros estudos que tratam de tal relação, Izabella Ao tratar da realização musical instrumental sob a ótica do movimento humano, Flora Maria Gomide Vezzá (2013, p. 15), afirma que "o corpo do músico posiciona-se para produzir um movimento que contenha em si as características da música -sonoridade, afinação, melodia, ritmo, expressividade, sentimento".…”
Section: O Acesso a Instituições De Ensino E O Vínculo Professor-alun...unclassified
“…The aim of this study was to explore the "dynamics and mechanisms" (Lee et al, 2011(Lee et al, , p. 1535 used by professional couples as they seek to navigate careers within the broader context of work, family, personal and community life. Previous research has shown that highly educated individuals are more likely to partner with those from similar educational backgrounds and to thus form a dual-career household (Wagner, 2006;Ackers and Gill, 2008;Bostr€ om et al, 2018). The focus of the study was on professionals in recognised fields such medicine, law, accounting and academia.…”
Section: Data Context and Collectionmentioning
confidence: 99%
“…Se, como vimos, a construção da identidade profissional é um contínuo que irá se estender ao longo da vida de cada um deles, passamos à discussão de A presença de um vínculo forte entre as figuras do professor e do aluno, portanto, é bastante documentada em pesquisas que acatam os universos esportivo, intelectual, universitário e científico (CAMPBELL, 2003;SCHNAIBERG, 2005;RESKIN, 1979;WAGNER, 2006). Ao revisar esses e outros estudos que tratam de tal relação, Izabella Ao tratar da realização musical instrumental sob a ótica do movimento humano, Flora Maria Gomide Vezzá (2013, p. 15), afirma que "o corpo do músico posiciona-se para produzir um movimento que contenha em si as características da música -sonoridade, afinação, melodia, ritmo, expressividade, sentimento".…”
Section: O Acesso a Instituições De Ensino E O Vínculo Professor-alun...unclassified